2021
DOI: 10.1186/s12893-021-01074-w
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of external vs internal pancreatic duct stents after pancreaticoduodenectomy in patients with FRS ≥ 4: a retrospective cohort study

Abstract: Background The prognostic value of external vs internal pancreatic duct stents after pancreaticoduodenectomy remains controversial. This study aimed to evaluate the benefits of external and internal stents using the Fistula Risk Score system with regard to the incidence of clinically relevant postoperative pancreatic fistula. Methods A total of 382 patients who underwent pancreaticoduodenectomy with duct to mucosa pancreaticojejunostomy were retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…17,18 The optimal stenting technique has also been studied comparing internal and external stents. The majority of published data indicate a more favorable outcome with external stents, 7,8,19 and this is especially true for patients with high risk, as described by Jiang and colleagues 20 who recently reported a better outcome with external stents in patients with a Fistula Risk Score of 4 or more. However, many studies have shown no difference.…”
Section: Introductionmentioning
confidence: 83%
“…17,18 The optimal stenting technique has also been studied comparing internal and external stents. The majority of published data indicate a more favorable outcome with external stents, 7,8,19 and this is especially true for patients with high risk, as described by Jiang and colleagues 20 who recently reported a better outcome with external stents in patients with a Fistula Risk Score of 4 or more. However, many studies have shown no difference.…”
Section: Introductionmentioning
confidence: 83%
“…14,28,29 Among numerous technical tricks and tips proposed to reduce POPF, the most extensively studied are anastomotic techniques, 25,30,31 use of sealant sponge, 2 reinforced stapler, 19 pancreatic stent, 32 omental flap 33,34 modalities of drainage, 35,36 or total pancreatectomy. 37 Regarding PD, externalized pancreatic drain seems the only technique able to reduce the rate of grade B to C POPF [38][39][40] but has not gained wide acceptance, maybe because of the risk of stent malfunction. 41 Also pancreaticogastrostomy could limit the risk of POPF comparatively to pancreaticojejunostomy, but with the downside of an increased risk of bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…However, initial randomized trials on the subject clearly demonstrated the ability of the technique to reduce morbidity and the incidence of clinically relevant PJA leaks, especially in patients at high risk of developing POPF [15][16][17]. Further research and high-quality evidence from systematic reviews and meta-analyses have confirmed the efficacy of transanastomotic external stents in reducing the incidence and grade of POPF in both randomized and nonrandomized settings [18][19][20][21]. The largest systematic review to date with meta-analysis of the POPF-related mortality rate includes 60,739 patients and undoubtedly confirmed that external transanastomotic stents decreased the POPF-related mortality rate [22].…”
Section: Transanastomotic External Pancreatic Duct Stentmentioning
confidence: 99%